Elastin Expression in Sacrouterina Ligament is Weaker in the Women with Pelvic Organ Prolapse - Hasnawati, Andi (Indonesian Socety of Obstetrics and Gynecology, 2012)
Objective: The research aims at comparing the elastin immunolabeling in the uterosacral ligaments in women with pelvic organ prolapse and without pelvic organ prolapse (POP). Methods: The research is done at Dr. Wahidin Sudirohusodo Hospital and education networking some hospitals the Obstetrics and Gynecological School of Medicine Hasanuddin University that began in January 2011 until April 2012. This research assessing expression of elastin on 35 women with a pop level III and IV and as control is 35 women without POP. Immunolabeling of elastin valued in staining checkings immunohistokimia uses antibodies elastin ( clone no. Ba-4 1:1600; Novacastra Laboratories Ltd, UK). The research was carried out by the cross sectional study. Mixed with chi-square. Level significance used is 0.05. Results: The results showed that the elastin immunolabeling in women with POP is decline on most sample expression with the intensity of elastin is weak (74.3%). The most control with the intensity of elastin immunolabeling is moderate (48.6%). Elastin immunolabeling seem significant in women with menopause and with BMI that overweight (all with p